Damage evaluation of a PCCP joint with a localized soil void and broken wires. Issue 14 (October 2021) - Li, Haizhen; Feng, Xin; Chen, Bozhi; Zhao, Lin
During the service life of a pipeline, the surrounding soil may erode locally around the pipe due to seepage and leakage, making the pipe partially unsupported and weakening the pipe–soil interaction. The presence of soil voids provides the possibility for broken wires and further accelerates damage. In this paper, the stress and strain of PCCP joint in service under a localized soil void and with broken wires were investigated using the general finite element software ABAQUS, and the structural damage of the pipe joint under superimposed defects was evaluated. The numerical model contained two PCCP segments, a flexible joint and the surrounding soil. The preliminary study suggests that the superimposed defects of a soil void and broken wires can cause increased damage to the PCCP joint. With the addition of the soil void, the micro cracks of both the concrete core and mortar coating transform into visible cracks, and the relative wire breakage rate with coupling defects is reduced by approximately 36% to reach the elastic limit state of the pipe. The findings of this research highlight the importance of good pipe–soil interactions and could provide a theoretical reference for damage assessment and further repair strategies.